Effects of an High-Fat Diet Enriched in Lard or in Fish Oil on the Hypothalamic Amp-Activated Protein Kinase and Inflammatory Mediators - Viggiano, Emanuela; Mollica, Maria Pina; Lionetti, Lillà; Cavaliere, Gina; Trinchese, Giovanna; De Filippo, Chiara; Chieffi, Sergio; Gaita, Marcello; Barletta, Antonio; De Luca, Bruno; Crispino, Marianna; Monda, Marcellino (Frontiers in Cellular Neuroscience, 2016)
The high fat diet rich in lard induces obesity, inflammation and oxidative stress, and the deregulation of hypothalamic nuclei plays an important role in this mechanism. One important factor involved in the food intake and inflammation is adenosine monophosphate-dependent kinase (AMPK), a serine/threonine kinase activated by phosphorylation. Omega (ω)3-polyunsaturated fatty acids (PUFA) are dietary compounds known to attenuate the obesity-related diseases, although the molecular mechanisms underlying their actions in the hypothalamus are not completely understood. We hypothesized that the beneficial effects of PUFA may be mediated by activation of AMPK in the hypothalamus. To this aim, rats were fed a control diet (CD), or isocaloric high fat diet containing either fish oil (FD; rich in ω3-PUFA) or lard (LD) for 6 weeks, and the activation of AMPK, inflammatory state (IKKβ, TNF-α) and oxidative stress (MDA, GSH/GSSG) were analysed in the hypothalamus. In addition, we also studied serum lipid profile, HOMA index, and pro-inflammatory parameters. Our results showed, at the hypothalamic level of LD-fed rats, an increase of AMPK activation, inflammation and oxidative stress, while no modifications were detected in FD-fed animals compared to CD. In addition a body weight gain, serum lipid profile, pro-inflammatory parameters and insulin resistance were reduced in FD animals compared to LD. In conclusion, our data indicate that the substitution of saturated by unsaturated fatty acids in the diet has beneficial effects on modulation of hypothalamic inflammation and function in obesity, underlying, at hypothalamic level, the interaction among insulin and/or leptin resistance, AMPK activation and hyperphagia.